Reproducibility of 7‐T brain spectroscopy using an ultrashort echo time STimulated Echo Acquisition Mode sequence and automated voxel repositioning. (8th October 2021) - Reid, Meredith A.; Forloines, Martha R.; Salibi, Nouha
Abstract : Establishing the reproducibility of brain MRS is important for clinical studies so that researchers can evaluate changes in metabolites due to treatment or the course of a disease and better understand the brain in healthy and disordered states. Prior 7‐T MRS reproducibility studies using the stimulated echo acquisition mode (STEAM) sequence have focused on the anterior cingulate cortex or posterior cingulate cortex and precuneus. The purpose of this study was to evaluate the reproducibility of metabolite measurements in the dorsolateral prefrontal cortex (DLPFC) using an ultrashort echo time (TE) STEAM sequence and automated voxel repositioning. Spectra were acquired during two scan sessions from nine subjects using the AutoAlign method for voxel repositioning. Reproducibility was evaluated with coefficients of variation (CVs) and percentage differences. The mean intrasubject CVs were less than 6% for the major metabolites glutamate, N‐acetylaspartate, total creatine, total choline, and myo‐inositol. The mean CVs were less than 20% for the smaller signals of GABA, glutamine, glutathione, and taurine. These results indicate that 7‐T MRS using a STEAM sequence with ultrashort TE and automated voxel repositioning provides excellent reproducibility of metabolites in the DLPFC. Abstract : Single‐voxel MR spectra were acquired from the dorsolateral prefrontal cortex of nine adults during two scan sessions using an ultrashort TE STEAM sequence at 7 T and automated voxel repositioning. Reproducibility was evaluated with coefficients of variation and percentage differences. The mean intrasubject CVs were less than 6% for the major metabolites, glutamate, N‐acetylaspartate, total creatine, total choline, and myo‐inositol and less than 20% for the smaller signals of GABA, glutamine, glutathione, and taurine.